2017
DOI: 10.1016/j.jtumed.2016.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Why are serum magnesium levels lower in Saudi dialysis patients?

Abstract: Objectives Serum magnesium (Mg) levels are often altered in dialysis patients. This study was conducted to ascertain the trends in Mg levels in patients on dialysis treatment. Methods A retrospective study was performed in the Dialysis Unit of King Khalid University Hospital, King Saud University, Riyadh, on patients undergoing regular dialysis. Patient demographic data, including body mass index (BMI), serum calcium (Ca), Mg, parathyroid hormone (PTH), cholesterol, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The hypomagnesium level was observed only in one patient. In a study by Ahmed H. Mitwalli et al 8 on serum magnesium (Mg) levels in CRF patients observed 10 patients (8.7%) had Mg levels of <0.7 mmol/L while 26 (23.9%) showed levels of >1.1 mmol/L. In the present study, it was observed that serum magnesium before dialysis was more (4.34± 1.38) compared to after dialysis (2.67 ±0.98) of patients with statistically significant correlation (p<0.05).…”
Section: Resultsmentioning
confidence: 99%
“…The hypomagnesium level was observed only in one patient. In a study by Ahmed H. Mitwalli et al 8 on serum magnesium (Mg) levels in CRF patients observed 10 patients (8.7%) had Mg levels of <0.7 mmol/L while 26 (23.9%) showed levels of >1.1 mmol/L. In the present study, it was observed that serum magnesium before dialysis was more (4.34± 1.38) compared to after dialysis (2.67 ±0.98) of patients with statistically significant correlation (p<0.05).…”
Section: Resultsmentioning
confidence: 99%
“…The subjects’ serum values of Mg, TC, and TG were determined, showing that patients that underwent peritoneal dialysis had lower Mg levels compared to hemodialysis patients. The correlation studies did not find statistically significant associations between Mg and TC or TG variations [ 130 ]. While studying the association of hypomagnesemia with increased mortality among patients that underwent peritoneal dialysis in a research which included two hundred and fifty three subjects, Cai et al (2016) reported a positive association between low serum Mg and TG (r = 0.160, p = 0.011), but the correlation with TC did not reach statistical significance ( p = 0.929) [ 131 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous experimental studies showed oral vitamin D in the treatment regimens had no significant effect on increasing serum Mg levels in laboratory samples (20)(21)(22)(23)(24)(25). In an experimental study on vitamin D deficient mice, the mice were assigned to six groups, each group receiving one of the 1,25-dihydroxyvitamin D3, 1,24,25-trihydroxyvitamin D3, 24,25-dihydroxyvitamin D3, a combination of the last two regimens, or vehicle (-D) for six days.…”
Section: Discussionmentioning
confidence: 98%
“…High doses of 25-hydroxyvitamin D increase Mg absorption; however, Mg is also absorbed regardless of vitamin D and its intestinal receptor (11). According to previous studies, several factors such as diabetes, certain medications, PPIs, thiazide diuretics, cisplatin, aminoglycoside antibiotics and calcineurin inhibitors (4,7,8), tubular defects (1) and type of dialysis (23) affect changes in Mg levels and the incidence of hypomagnesemia.…”
Section: Discussionmentioning
confidence: 99%